Ectodermal disturbance in development shared by anorexia and schizophrenia may reflect neurodevelopmental abnormalities. Issue 10 (12th September 2021) - Remberk, Barbara; Niwiński, Piotr; Brzóska‐Konkol, Ewa; Borowska, Anna; Papasz‐Siemieniuk, Anna; Brągoszewska, Joanna; Bażyńska, Anna Katarzyna; Szostakiewicz, Łukasz; Herman, Anna
Abstract: Minor physical abnormalities (MPA) are subtle dysmorphic features of bodily structures that have little or no impact on function. Most MPA develop during the first gestational trimester and are considered as important indicators of neuroectodermal deficiencies emerging during early brain development. A higher frequency of MPA was confirmed in schizophrenia patients and their relatives, when compared to controls. These findings are consistent with the neurodevelopmental model of schizophrenia. A neurodevelopmental component amongst other risk factors has also been recently proposed for anorexia nervosa (AN). The current study aimed to assess MPA frequency in adolescent inpatients with either schizophrenia spectrum disorders (SSD) or AN as compared to healthy controls (HC). The Waldrop Scale was used for assessing MPA. The mean MPA total score and mean head subscore was significantly higher in both test groups than in HC. There were no statistically significant differences between SSD and AN groups. The MPA profile (not frequency) was similar in all three groups. This finding is consistent both with widely acknowledged neurodevelopmental schizophrenia hypothesis as well as with more recent neurodevelopmental model of AN. Nevertheless, the findings should not be overgeneralized and further studies are warranted. Abstract : Minor physical abnormalities (MPA) may indicate neuroectodermal developmental deficiencies. MPA frequency was assessed in adolescents with schizophrenia spectrum disorders (SSD) anorexia nervosa (AN) and healthy controls (HC). The mean MPA score was significantly higher in both test groups than in HC. The results are consistent with neurodevelopmental schizophrenia hypothesis and indicate neurodevelopmental etiological component in anorexia nervosa.